Rotation properties of feather shuttlecocks in motion - Cao, X.; Qiu, J.; Zhang, X.; Shi, J. (Procedia Engineering, 2014)
Feather shuttlecocks are chiral bodies whose rotation properties, such as trajectory and velocity, affect their motion states. This study proposes an experimental method to simulate the rotation properties of shuttlecocks. The effect of wind velocity on the angular velocity of refitting shuttlecocks is tested in a wind tunnel. The refitting parts lie on the cork of the shuttlecocks to avoid affecting the shape of the feather and the friction between air and the feather. Two types of moments are assumed to act on the shuttlecocks: driving and resistance. The driving moment is dependent on relative airflow velocity, whereas the resistance moment is related to rotation speed. Basing on wind tunnel experimental data, we illustrate the curves of the resistance and driving moments. Results provide theoretical guidance in the design of synthetic shuttlecocks and analysis of badminton techniques.